2015
DOI: 10.1007/s00415-015-7652-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus in cerebral venous thrombosis

Abstract: Increased intracranial pressure is common in cerebral venous thrombosis (CVT), but hydrocephalus is rarely reported in these patients. We examined the frequency, pathophysiology and associated clinical manifestations of hydrocephalus in patients with CVT admitted to our hospital between 2000 and 2010 (prospectively since July 2006). Hydrocephalus was defined as a bicaudate index larger than the 95th percentile for age, and/or a radial width of the temporal horn of ≥5 mm. We excluded patients in whom hydrocepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…12 Zuurbier et al reported a 15.1% incidence of hydrocephalus secondary to a spontaneous cerebral sinus thrombosis. 16 In the present study, hydrocephalus, requiring internal CSF diversion but not leading to permanent impairment, appeared in 2 of 12 patients (16.7%) with a postoperative lateral sinus thrombosis. However, the exact origin of the hydrocephalus is a matter of debate during the early postoperative period because the underlying disease, surgical procedure, and location of the lesion may equally account for it.…”
Section: Consequences Of Postoperative Lateral Sinus Thrombosissupporting
confidence: 42%
“…12 Zuurbier et al reported a 15.1% incidence of hydrocephalus secondary to a spontaneous cerebral sinus thrombosis. 16 In the present study, hydrocephalus, requiring internal CSF diversion but not leading to permanent impairment, appeared in 2 of 12 patients (16.7%) with a postoperative lateral sinus thrombosis. However, the exact origin of the hydrocephalus is a matter of debate during the early postoperative period because the underlying disease, surgical procedure, and location of the lesion may equally account for it.…”
Section: Consequences Of Postoperative Lateral Sinus Thrombosissupporting
confidence: 42%
“…[1][2][3] Several studies have examined common post-operative complications of VS tumor resections, such as cranial nerve function, infection, and cerebrospinal fluid (CSF) leaks. 4,5 The incidence of these complications is typically compared with various factors including demographics, surgical approach, and operative time. 4,6 However, there is limited data on the incidence, clinical progression, and proper management of potentially fatal dural venous sinus thrombosis (DVST) after VS tumor resections.…”
Section: Introductionmentioning
confidence: 99%
“…122 In a recent case series of 14 CVT patients with acute hydrocephalus only one patient had a shunt. 121 Despite shunting the patient died.…”
Section: (Recommendations)mentioning
confidence: 99%
“…Mild ventricular enlargement can be found in thrombosis of the deep venous system due to thalamic oedema and in the contralesional side in CVT complicated by large hemispherical lesions. 121 In the literature review we found 736 titles, from which we selected 30 full text articles and included 10 studies. Studies were case reports, case series and a systematic review of cases.…”
Section: (Recommendations)mentioning
confidence: 99%